2019
DOI: 10.1051/0004-6361/201936547
|View full text |Cite
|
Sign up to set email alerts
|

Local Bubble contribution to the 353-GHz dust polarized emission

Abstract: It has not been shown so far whether the diffuse Galactic polarized emission at frequencies relevant for cosmic microwave background (CMB) studies originates from nearby or more distant regions of our Galaxy. This questions previous attempts that have been made to constrain magnetic field models at local and large scales. The scope of this work is to investigate and quantify the contribution of the dusty and magnetized local interstellar medium to the observed emission that is polarized by thermal dust. We use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 55 publications
2
13
1
Order By: Relevance
“…Similar regions of alignment are found in the |θ − χ dust | map. This is not a surprise, since at high latitudes, the absorbing and emitting dust column is likely the same (as shown by Skalidis & Pelgrims 2019;Planck Collaboration et al 2020b). At high latitudes, the large areas of alignment are particularly above the Galactic centre near Loop I.…”
Section: Large-scale Overview and Choice Of Loopssupporting
confidence: 58%
“…Similar regions of alignment are found in the |θ − χ dust | map. This is not a surprise, since at high latitudes, the absorbing and emitting dust column is likely the same (as shown by Skalidis & Pelgrims 2019;Planck Collaboration et al 2020b). At high latitudes, the large areas of alignment are particularly above the Galactic centre near Loop I.…”
Section: Large-scale Overview and Choice Of Loopssupporting
confidence: 58%
“…Similar regions of alignment are found in the |θ − χ dust | map. This is not a surprise, since at high latitudes the absorbing and emitting dust column is likely the same (as shown by Skalidis & Pelgrims 2019;Collaboration et al 2020b). At high latitudes, the large areas of alignment are particularly above the Galactic center near Loop I.…”
Section: Large-scale Overview and Choice Of Loopsmentioning
confidence: 68%
“…The map might also prove relevant for foreground corrections to the CMB, especially for CMB polarization studies. It was shown that most of the Galactic infrared polarization at high latitudes (|b| > 60) comes from close-by regions around 200-300 pc (Skalidis & Pelgrims 2019). Correction maps have so far been based on infrared observations, and could be biased through different starlight illumination or differing dust temperatures.…”
Section: Introductionmentioning
confidence: 99%